Players' work time : a history of the British Musicians' Union, 1893-2013 - Cloonan, Martin; Williamson, John, 1949- (Manchester University Press, 2016)
This book examines the working lives of musicians over the past 120 years via the history of the Musicians' Union. The union has been at the centre of all major agreements covering the employment of musicians across the UK's music industries for this period and its role to date has largely been ignored by historians of the music profession, the music industries and trade unions. This book remedies that oversight, providing fresh insight to musicians' working lives, the industries in which they work and wider British social life. It explores a history of confrontation, coercion and compromise played out across the nation's studios, performance spaces and airwaves.